2015
DOI: 10.1515/eng-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Flow of River Tigris and its Effect on the Bed Sediment within Baghdad, Iraq

Abstract: River Tigris is a major river in Iraq. Sediment at the bed of the river within a reach of about 18 km from the center of Baghdad upstream was investigated. Sixty five cross sections were surveyed, and 46 sediment samples were collected and analyzed. It was noticed that fine sand was dominant in the bed (90.74%). The average median size within the reach was 2.49 phi (0.177 mm), while the mean size was 2.58 phi (0.16 mm). In addition, the sediments were moderately sorted, fine skewed and leptokurtic. The size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The size of the bed sediment was less than in earlier investigations (see Al-Ansari and Toma 1984). In addition, the sediments were moderately well sorted, finely skewed and leptokurtic (Al-Ansari et al 2015). Geohydraulique (1977) concluded that the Tigris River sediment is 'bed-load' (bed-material load), since the suspended load concentrations never reached 3 g/l in high flows and never exceeded 0.2 g/l in low water periods.…”
Section: River Geometry and Bed Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the bed sediment was less than in earlier investigations (see Al-Ansari and Toma 1984). In addition, the sediments were moderately well sorted, finely skewed and leptokurtic (Al-Ansari et al 2015). Geohydraulique (1977) concluded that the Tigris River sediment is 'bed-load' (bed-material load), since the suspended load concentrations never reached 3 g/l in high flows and never exceeded 0.2 g/l in low water periods.…”
Section: River Geometry and Bed Compositionmentioning
confidence: 99%
“…These data sets were determined by direct measurements and analysis of sampled sediment. The results published by Al-Ansari et al (2015) contained most of the datasets, while other datasets were tabulated in Table 4.…”
Section: Appendix Amentioning
confidence: 99%
“…The adjustment of the Manning friction coefficient was used to match water level to field data. About 74% of the Tigris River bed within Mosul city is very coarse gravel (Othman and Deguan 2004), while the bed of the Tigris River within Baghdad city is mainly covered by sand (Ali et al 2012;Al-Ansari et al 2015). Manning coefficients in the Tigris River (Table 5) were selected based on values reported by Chow (1959).…”
Section: The Tigris Rivermentioning
confidence: 99%
“…Some researchers have developed relationships with the sediment transport depending upon the amount of discharge passing through the river. The annual sediment load passing through the Euphrates River within Al Anbar province for various studies was estimated to be between 1.9 * 10 6 tonne/year and 2.1 * 10 7 tonne/year (Al-Ansari et al 2015Al-ansari et al 1988;Khassaf and Al-Rahman 2005;Sulaiman et al 2019b).…”
Section: Introductionmentioning
confidence: 99%